Artificial Intelligence (AI) & Ethics Profiling (Akeru, Bunka, Syuu kan, Sai seisan) - Gamayanto, Indra; Wibowo, Sasono (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2023)
AI faces many challenges in the future. Some people still say that AI is a threat to the future, but on the other hand, AI is a technology that will help many people live their lives. In this concept research, we will explain what we think about AI and what ethics should be involved in using AI. It will require a lot of analysis to produce a concept of AI ethics, which is not easy. Our focus will provide perspectives from the social, psychological, and cultural sides and what things might affect human life by quickly developing AI. The final result of this concept is a framework for the ethics of AI profiling, where this may be used as a guide or opinion that can be considered when we use AI in our daily lives. AI is something that must be supported, and its application must receive special attention so that it can help humans in solving various life problems.